PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA KLINIK HOUSE OF PHYTO SEMARANG (Students' Journal of Economic and Management, 2014)
The purpose of the study titled "The Effect of Service Quality and Corporate Image on Customer Satisfaction ( Study At House Of Phyto Clinic in Semarang ) " is to examine and analyze the effect on the image quality of service and customer satisfaction .Data used in this study is primary data obtained directly from the original source . While the techniques used to collect data using a questionnaire by asking a number of written questions used to obtain information of the respondents. The sample used in this study were 100 respondents with sempel retrieval technique was purposive sampling , the criteria respondents who become customers clinic House of phyto ( already doing more treatments of1 times ) dijalain Brotojoyo 4D/15 cottage Indraprasta Semarang . The collected data were analyzed by using AnalisisFaktor to test the validity of the question items , Cronbach 's Alpha formula for reliability testing instruments and multiple linear regression analysis .The results of the hypothesis : ( 1 ) Quality of service and no significant positive effect on the customer satisfaction ( 2 ) Corporate Image and significant positive effect on customer satisfaction . Keywords : Quality of Service , Image , and Customer Satisfaction